2016
DOI: 10.1159/000452819
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Lipids

Abstract: Human milk lipids provide the infant with energy and essential vitamins, polyunsaturated fatty acids, and bioactive components. Adding complex lipids and milk fat globule membranes to vegetable oil-based infant formula has the potential to enhance infant development and reduce infections. Cholesterol provision with breastfeeding modulates infant sterol metabolism and may induce long-term benefits. Some 98-99% of milk lipids are comprised by triacylglycerols, whose properties depend on incorporated fatty acids.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
233
4
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(301 citation statements)
references
References 71 publications
14
233
4
19
Order By: Relevance
“…However, the levels of carbohydrates in Mother 1 decreased progressively. The dynamics of the energy content corresponded with the dynamics of fat since fat content represents 40-50 % of the energy intake (14).…”
Section: Discusionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the levels of carbohydrates in Mother 1 decreased progressively. The dynamics of the energy content corresponded with the dynamics of fat since fat content represents 40-50 % of the energy intake (14).…”
Section: Discusionmentioning
confidence: 90%
“…Total energy intake is proportional to the contents of fat and carbohydrates. Fat and carbohydrate represent almost 90 % of total energy content of breast milk (14).…”
Section: Discusionmentioning
confidence: 99%
“…24 Furthermore they are an important source of essential nutrients such as polyunsaturated fatty acids (PUFA), lipid soluble vitamins, complex lipids and bioactive compounds. 25 …”
Section: Lipidsmentioning
confidence: 99%
“…However, persistent changes in dietary supply lead to modification of maternal stores. 25,28 LCPUFAs exert several major biological effects, particularly on membrane functions, eicosaenoid and docosanoid production and related physiological processes, including growth and immune response. Human milk lipids, particularly medium chain monoglycerides, have been found to inactivate several pathogens in vitro, including Group B streptococcus, thus contributing to the protection against invasive infections.…”
Section: Lipidsmentioning
confidence: 99%
“…Koletzko et al concluded by noting that breastfeeding provides both ARA and DHA [91], which compensates for low LCPUFA synthesis in carriers of some FADS gene polymorphisms. Infants with gene-linked low ARA synthesis consuming formula without additional ARA might be at greater risk of asthma, eczema, or other allergic diseases and possibly suboptimal cognitive development [67,92].…”
Section: Interaction Of Infant Diet and Fads Gene Polymorphisms On Comentioning
confidence: 99%